Communication effectiveness influence the organization's performance: a case study of Kota Setar police district - Mohd Redzuan, Salleh (2021)
This study investigates some factors that influence organization performance. Communication effectiveness is one of the factors that will impact to the performance of an organization. There are two types of communication that being practiced: effective communication, and ineffective communication. These two types of communication are the independent variables in this study. The independent variables are being studied to see the relationship with the dependent variable, performance of organization. This study focuses on the Royal Malaysia Police personnel in Kota Setar Police District who are responsible to enforce the rules and at the same time to serve customers. To make sure rules and regulations can be enforced, the personnel involved must understand effective communication. This study will find out the relationship between independent variables and dependent variable in order to make sure the organization is still relevant, and performs well. The questionnaire was distributed to all the personnel in Kota Setar Police District involving every department with different work experienced and others. Data collected were analyzed using Statistical Package for Social Science (SPSS) 26.0. The results will show the relationship between independent variables and dependent variable. As a conclusion, effective communication and ineffective communication are both related to the performance of an organization.